2017
DOI: 10.1038/s41598-017-01880-4
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking during homodimeric assembly activates an E3 ubiquitin ligase

Abstract: C-terminus of Hsc/p70-Interacting Protein (CHIP) is a homodimeric E3 ubiquitin ligase. Each CHIP monomer consists of a tetratricopeptide-repeat (TPR), helix-turn-helix (HH), and U-box domain. In contrast to nearly all homodimeric proteins, CHIP is asymmetric. To uncover the origins of asymmetry, we performed molecular dynamics simulations of dimer assembly. We determined that a CHIP monomer is most stable when the HH domain has an extended helix that supports intra-monomer TPR-U-box interaction, blocking the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…The Carboxyl terminus of Hsc70 interacting protein (CHIP) cDNA encodes a 34.5 kDa wellconserved protein that has around 98% sequence similarity with the mouse and ∼60% similarity with the fruit fly 31 . CHIP contains a conserved U-box domain at their C terminus having E3 ligase activity and an N terminal tetratricopeptide repeat (TPR) domain responsible for interaction with Hsc/p70 and HSP90 clients 32,33 . An earlier study demonstrated the protective effect of CHIP against myocardial injury induced apoptosis and oxidative stress in the CHIPsufficient animal model 34 .…”
Section: Introductionmentioning
confidence: 99%
“…The Carboxyl terminus of Hsc70 interacting protein (CHIP) cDNA encodes a 34.5 kDa wellconserved protein that has around 98% sequence similarity with the mouse and ∼60% similarity with the fruit fly 31 . CHIP contains a conserved U-box domain at their C terminus having E3 ligase activity and an N terminal tetratricopeptide repeat (TPR) domain responsible for interaction with Hsc/p70 and HSP90 clients 32,33 . An earlier study demonstrated the protective effect of CHIP against myocardial injury induced apoptosis and oxidative stress in the CHIPsufficient animal model 34 .…”
Section: Introductionmentioning
confidence: 99%
“…(1) Each monomer is composed of a TPR domain (pink cube), a U-box domain (green sphere), and a dimerization domain (blue cylinders). Molecular dynamics studies 50 have shown that the monomer in solution is stabilized through TPR-Ubox interactions which block the E2 binding site (X). (2) In the dimer, the two helix-coils come together such that one bends and generates two smaller, kinked helices.…”
Section: Discussionmentioning
confidence: 99%
“…This apparent discrepancy has been explained by a model of conformational flexibility 49 , in which the CHIP dimer switches between two opposed asymmetric conformations (Figs 2 , 4 and 8c ) through a short-lived, symmetric conformation (Figs 3 and 8c ). A recent molecular dynamics simulation with the CHIP monomer and dimer 50 calculated that a monomer in solution would be most stable when the TPR and U-box domains interact, which would occlude the E2 binding site (Figs 1 and 8c ). Such a monomer would thus be non-functional, and CHIP E3 ligase activity could only be activated after dimer formation, when one of the two E2 binding sites would become accessible to the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“… 47 The structure of dimeric mouse CHIP reveals an unusual asymmetry in which the protomers adopt radically different conformations 48 and breaking of symmetry during homodimeric assembly induces E3 ubiquitin ligase activity. 49 As a consequence of this asymmetric arrangement, one of the 2 catalytical U-box domains is sterically hindered and not accessible for E2 enzyme binding. Thus, the asymmetric structure of the CHIP dimer provides an elegant means for coupling a dimeric chaperone to a single ubiquitylation system, supporting the formation of a monotonic polyubiquitin chain.…”
Section: Future Directions – Mechanisms Modifying Chip Activity and Smentioning
confidence: 99%